Fecal Short-Chain Fatty Acid Ratios as Related to Gastrointestinal and Depressive Symptoms in Young Adults. Issue 7 (September 2021) - Müller, Bettina; Rasmusson, Annica J.; Just, David; Jayarathna, Shishanthi; Moazzami, Ali; Novicic, Zorana Kurbalija; Cunningham, Janet L.
ABSTRACT: Objective: Short-chain fatty acids (SCFAs) are produced by the gut microbiota and may reflect health. Gut symptoms are common in individuals with depressive disorders, and recent data indicate relationships between gut microbiota and psychiatric health. We aimed to investigate potential associations between SCFAs and self-reported depressive and gut symptoms in young adults. Methods: Fecal samples from 164 individuals (125 were patients with psychiatric disorders: mean [standard deviation] age = 21.9 [2.6] years, 14% men; 39 nonpsychiatric controls: age = 28.5 [9.5] years, 38% men) were analyzed for the SCFA acetate, butyrate, and propionate by nuclear magnetic resonance spectroscopy. We then compared SCFA ratios with dimensional measures of self-reported depressive and gut symptoms. Results: Depressive symptoms showed a positive association with acetate levels (ρ = 0.235, p = .003) and negative associations with both butyrate (ρ = −0.195, p = .014) and propionate levels (ρ = −0.201, p = .009) in relation to total SCFA levels. Furthermore, symptoms of diarrhea showed positive associations with acetate (ρ = 0.217, p = .010) and negative associations with propionate in relation to total SCFA levels (ρ = 0.229, p = 0–007). Cluster analysis revealed a heterogeneous pattern where shifts in SCFA ratios were observed in individuals with elevated levels of depressive symptoms, elevated levels of gut symptoms, or both. Conclusions: Shifts in SCFAs are associated with both depressive symptoms and gut symptoms in young adults and may have of relevance for treatment. Abstract : Supplemental digital content is available in the text.